Driving Digital Financial Transformation: The Role of Accounting Proficiency and Government Support on Intention to Use Financial Applications - Samsiah, Siti; Aristi, Mentari Dwi; Sari, Dian Puji Puspita; Rikinorhakis Ridzwan (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study aims to analyse the influence of accounting proficiency and government support on the intention to use financial applications in micro, small, and medium enterprises (MSMEs) in the culinary sector in Riau Province. This study uses a quantitative approach with a survey method for MSMEs who are familiar with financial applications. The data were analysed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) method with the help of SmartPLS software. The results of the study show that both accounting proficiency and government support have a positive and significant effect on the intention to use financial applications. These findings indicate that the accounting skills of business owners and the support from the government in the form of training, policies, and digital infrastructure can encourage the intention of business owners to adopt accounting technology more widely. The implications of this research support input for the government and MSMEs institutions in designing digital-based MSMEs empowerment strategies.